Methodical apparatus for risk assessment in decision-making to combat illegal migration at the state border of Ukraine - Bloshchynskyi, Ihor; Meiko, Oleksandr; Zalozh, Victor; Andrushko, Volodymyr; Voitiuk, Olena (Edelweiss Applied Science and Technology, 2024)
This study proposes a methodical apparatus for risk assessment when making decisions on combating illegal migration at the state border of Ukraine. This apparatus includes a risk assessment methodology, a set of risk assessment indicators and criteria for combating illegal migration, a model of illegal migration risk assessment and a model for choosing the processing method. The goal that was set during the methodology development involves the following main stages: forming a set of indicators and criteria for risk assessment, assessment of the threat impact level (assessment of the threat probability level and the level of the threat’s negative consequences), vulnerability assessment, determining the risk level and the processing method. An expert survey of analysts from the Ukrainian Border Guard Agency was carried out to develop this set of risk assessment indicators and criteria. The proposed set includes new indicators, mathematical assessment models, quantitative values of assessment criteria and considers the influence weight of the main factors on the threat and vulnerability levels. This provides an opportunity to bring the qualitative characteristics of the risk level indicator to the provisions of modern risk management theory to obtain the quantitative value of the risk level, to exclude a subjective factor in assessment and to determine the risk level more accurately. The improved methodical apparatus allows developing of an action strategy aimed at minimizing the negative consequences of risk when making management decisions to combat illegal migration to assess a risk management result using an economic effect indicator.